2013
DOI: 10.3349/ymj.2013.54.1.87
|View full text |Cite
|
Sign up to set email alerts
|

The Change of Prostate Cancer Treatment in Korea: 5 Year Analysis of a Single Institution

Abstract: PurposeWe analyzed changes to the trends of prostate cancer management and patient characteristics at a single institute during 5 years due to the significant increase of the prostate cancer incidence and the robotic equipment in Korea.Materials and MethodsProstate cancer patient data from a single institute recorded from 2006 to 2010 were analyzed. Cancer stage, initial treatment modalities, and the pattern of outpatient clinical management were reviewed.ResultsBetween 2006 and 2010, 386 prostate cancers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Several recent studies have noted increasing use of RP. 15,16 A Korean study found that the rates of RP for all patients diagnosed with prostate cancer increased from 43% in 2006 to 62% in 2010. 15 This increase in use of prostatectomy, coupled with the associated decrease in radiation use, may largely be due to new surgical techniques and improved side effect profiles.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several recent studies have noted increasing use of RP. 15,16 A Korean study found that the rates of RP for all patients diagnosed with prostate cancer increased from 43% in 2006 to 62% in 2010. 15 This increase in use of prostatectomy, coupled with the associated decrease in radiation use, may largely be due to new surgical techniques and improved side effect profiles.…”
Section: Discussionmentioning
confidence: 98%
“…15,16 A Korean study found that the rates of RP for all patients diagnosed with prostate cancer increased from 43% in 2006 to 62% in 2010. 15 This increase in use of prostatectomy, coupled with the associated decrease in radiation use, may largely be due to new surgical techniques and improved side effect profiles. For instance, minimally invasive RP with laparoscopy has been shown to decrease the need for blood transfusions, postoperative bleeding, reoperations and length of stay, as compared with more traditional operations.…”
Section: Discussionmentioning
confidence: 98%
“…With widespread prostate-specific antigen (PSA) screening, localized prostate cancer has exhibited the greatest increases in incidence rate among prostate cancer cases 2. PSA screening has facilitated discovery of a higher incidence of prostate cancer, as well as stage migration 3.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer incidence is very high in the United States and Europe, where prostate-specific antigen (PSA) screening is most common. Recently, there has been a rapid increase of the incidence of prostate cancer in Korean due to an increase in PSA screenings even though the incidence in Asia is lower than in Western countries 1,2. The European Randomized Screening of Prostate Cancer (ERSPC)3-5 and the Prostate Cancer Prevention Trial (PCPT)6,7 have each introduced online prostate cancer risk calculators (RC).…”
Section: Introductionmentioning
confidence: 99%